INTEGRATION OF GLOBAL EU TRANSPORT TRENDS IN UKRAINE: UPDATING THE REGULATORY FRAMEWORK - Polishchuk, Inna; Tkachuk, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: the article is devoted to defining and analyzing the current state of updating the regulatory framework of Ukraine in the transport sector according to the criteria of integration of global transport trends of the European Union. Methods: the study is based on the methods of cognition, analysis and synthesis, as well as systemic and structural, formal and logical, and comparative legal methods. Results: it is substantiated that for our country at the present stage of its development, the need to integrate global transport trends of the European Union is of key importance for the development of the national transport system, transport network, and restoration of transport potential. These tasks cannot be solved without the regulatory influence of the state and improvement of the relevant regulatory framework, which needs to be updated to meet the requirements of the EU-Ukraine Association Agreement, EU Directives and Regulations on transport, and bilateral agreements. Currently, a number of Ukraine’s existing commitments and legislative initiatives are aimed at bringing the parameters of the national transport system in line with European norms and standards. However, in the new socio-economic conditions, there is a need to rethink the development of Ukraine’s transport policy in the context of the formation of a European integrated transport system based on the interaction of different modes of transport. The article identifies the main areas of adaptation and updating of Ukraine’s transport legislation: development of regulations and improvement of the regulatory framework to meet the requirements of the EU Transport Directives; Ukraine’s participation in European transport organizations and accession to conventions, protocols and treaties, implementation of resolutions and recommendations adopted by these organizations; preparation and conclusion of bilateral intergovernmental agreements in the field of transport between Ukraine and European countries. Discussion: identification of priority issues for completing the harmonization of national transport legislation with EU norms and regulations, the need to adopt draft laws on the establishment of transport hubs in Ukraine, the creation of an effective legal framework for combined (intermodal) transportation, the Roadmap for the Development of the Unified Transport System of Ukraine, and the creation of conditions for the functioning of a well-established system of transport and logistics outsourcing, improving state mechanisms for regulating relevant aspects of the sectoral European integration of certain types of transport into the EU internal market, strengthening the levers of state policy in the field of transport to ensure conditions for Ukraine’s post-war recovery.